A Study of the Effect of Condenser Type on a Performance of Solar Linear Fresnel Power Plant in Sebha City - Sharif, Mohamed; Ibrahim Mohamed Ibrahim Eslayem (Journal of Pure & Applied Sciences, 2022)
This study compares two standard condensers used in electric power plants and examines how they affect a 100 MW solar thermal power plant. The factory uses Fresnel mirrors as a thermal collector and Hitec as a heat transfer fluid in the solar field. Using the System Advisor Model program, the plant performance was designed and modeled, as well as the cycle performance evaluation and energy cost for each type. The results showed a remarkable convergence in the efficiency of the plant as well as the Levelized cost of energy. The study concluded that it is possible to replace the evaporator condensers with air-cooled condensers, with an increase of 6.2% of the Levelized cost of energy, and this percentage is not large compared to the considerable amount of water needed by the water-cooled condensers.